Comparison of Optic Disc Parameters in Hyperopic and Emmetropic Eyes of Healthy Children with HRT and OCT - Wenner, Yaroslava; Brauer, Vanessa; Kunze, Kira; Besgen, Volker; Kuhli-Hattenbach, Claudia; Bertelmann, Thomas; Sekundo, Walter (Klinische Monatsblätter für Augenheilkunde, 2018)
Purpose To investigate, through Heidelberg retina tomography II (HRT II) and RTVue-100 optical coherence tomography (OCT), normal parameters of the optic nerve head (ONH) in highly hyperopic children, and compare these with a group of children with low hyperopia and emmetropia, as fundus examination of highly hyperopic children often shows crowding of the optic disc, which may be difficult to distinguish from mild optic disc swelling.Patients and Methods ONH of the higher hyperopic eye was examined with HRT II and the peripapillary nerve fiber layer (RNFL) with RTVue-100, in 6 to 15-year-old full-term children with normal visual acuity and spherical equivalent ≥ + 3.0 D (hyperopic group) and < + 3.0 to − 1.0 D (emmetropic group).Results Thirty highly hyperopic children and 33 emmetropic controls had a mean spherical equivalent of + 5.1 ± 1.5 D and a mean age of 8.4 ± 2.8 years, and + 1.0 ± 1.2 D and 9.6 ± 2.6 years, respectively. There was no significant difference in OCT-assessed RNFL thickness between the two groups. Compared to the emmetropic group, following HRT parameters were significantly smaller in the hyperopic group: Disc area (1.41 vs. 1.68 mm2, p = 0.023), cup area (0.19 vs. 0.37 mm2, p = 0.0001), cup volume (0.03 vs. 0.08 mm3, p = 0.02), cup/disc area (0.13 vs. 0.20, p = 0.006), linear cup/disc (0.33 vs. 0.42, p = 0.004), and mean cup depth (0.13 vs. 0.17 mm, p = 0.019).Conclusion In children, ONH of highly hyperopic eyes are smaller than those of emmetropic eyes. RNFL thickness and neural rim volume are similar to emmetropic eyes. They can therefore appear more crowded.
Keywords: children; optic nerve; HRT; OCT; hyperopia